2013
DOI: 10.1161/hypertensionaha.111.00698
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Retinal Microvascular Caliber and Blood Pressure During Pregnancy

Abstract: The microvasculature plays an important role in regulating cardiovascular changes in pregnancy, but changes in microvasculature have been difficult to document in vivo. This study objectively quantifies changes in the maternal retinal arteriolar and venular caliber over the course of healthy pregnancy. Healthy pregnant women (n=53) were recruited from Royal Prince Alfred Hospital, Sydney, Australia. Retinal images and mean arterial blood pressures (MAP) were collected at 13, 19, 29, and 38 weeks of gestation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
18
2
4
Order By: Relevance
“…We have previously described retinal microvascular and blood pressure changes throughout healthy pregnancy in the same cohort. 17 In healthy pregnancy, dilatation of the retinal arterioles and venules was observed between weeks 13 and 19, and this occurred concurrently with a decrease in MAP. Combining these measurements as the cCRAE and the cCRVE, respectively, allowed quantification of the decrease in peripheral resistance experienced within the maternal circulation during gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described retinal microvascular and blood pressure changes throughout healthy pregnancy in the same cohort. 17 In healthy pregnancy, dilatation of the retinal arterioles and venules was observed between weeks 13 and 19, and this occurred concurrently with a decrease in MAP. Combining these measurements as the cCRAE and the cCRVE, respectively, allowed quantification of the decrease in peripheral resistance experienced within the maternal circulation during gestation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Because blood pressure is known to affect retinal vascular caliber, 16 retinal vascular measures were corrected for MAP by dividing the CRAE and CRVE by MAP to produce the cCRAE and cCRVE, respectively. 17 Retinal image graders were blinded to the pregnancy outcome. To determine intergrader reliability, a subset of 40 retinal images were randomly selected and independently measured by 2 graders.…”
Section: Retinal Image Analysismentioning
confidence: 99%
“…Several papers have been published on the physiological changes in fundus retinal vascular caliber [5]. A cohort study of patients with normal pregnancies reported that fundus imaging allowed observation of retinal vascular calibers over time and in the 2nd trimester of pregnancy, blood vessel caliber increases showed negative correlations with mean arterial pressures (MAP) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study of patients with normal pregnancies reported that fundus imaging allowed observation of retinal vascular calibers over time and in the 2nd trimester of pregnancy, blood vessel caliber increases showed negative correlations with mean arterial pressures (MAP) [5]. Moreover, narrowing of retinal microvascular calibers has been reported to precede the onset of preeclampsia and increases in blood pressure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional results from the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) study support these adaptations, showing that each 10 mmHg increase in MAP during pregnancy was associated with a significant reduction in retinal arteriolar caliber, especially for MAP ≥90 mmHg [ 28 ]. Another study, using retinal images obtained throughout pregnancy and 6 months after pregnancy of 53 normotensive women, also demonstrated changes in the retinal microvasculature over the course of a normotensive pregnancy in conjunction with blood pressure adaptations [ 29 ]. During mid-pregnancy, when blood pressure shows a physiologic decrease, retinal arteriolar and retinal venular calibers increased significantly.…”
Section: Discussionmentioning
confidence: 99%